National Incidence Studies of Missing, Abducted, Runaway, and Thrownaway Children (NISMART), 1988 - Finkelhor, David ([Verlag nicht ermittelbar], 1992)
This collection was undertaken in response to the mandate of the 1984 Missing Children Act. The objective of the act was to estimate the incidence of five categories of children: children abducted by family members, children abducted by nonfamily members, runaways, thrownaways (those not wanted by their families or taken from families because of abuse or neglect), and children considered missing. Data were collected by several different methods. The centerpiece of this collection is a household survey (Parts 19, 20, and 35) that interviewed families to determine whether any children fit the categories under study. Basic demographic information on age, race, and sex was collected, and questions on the family situation were asked of identified children and their parents and siblings. A survey of juvenile facilities (Parts 28 and 29) was also conducted to determine how many children had run away from these facilities. Facility administrators were prompted for demographic information on the runaways as well as for information on the structure of the runaways' families. In addition, a survey of returned runaways (children who had run away and returned home) (Part 30) was completed to find out whether children's accounts of runaway episodes matched the accounts given by their parents. Children were queried about their relationships with their parents and their views of their contributions to the family. They were also asked about each specific runaway episode: whether they actually ran away or were asked to leave, how long the episode lasted, whether friends knew about it, whether friends accompanied them, whether they used drugs before, during, or after the episode, how they were found, where they were found, and whether disciplinary action was taken. The police records component (Parts 31-33) contains information on homicides, abductions, and sexual assaults.